ANALISIS LOSS OF HETEROZYGOSITYGEN RAR β2 PADA PATOGENESIS KANKER PAYUDARA - Muliartha, I Ketut Gede; Riawan, Wibi; Hidayat, Asnah; Armania, Fitri (Fakultas Kedokteran Universitas Brawijaya, 2008)
The aim of this research was to investigate the event of loss of heterozygosity of retinoid acid receptor (RAR β2) gene on the chromosom 3p24 in the pathogenesis ofbreast cancer. The breast cancer is the most malignant tumor that leads the second cause of death among the female. The recent concept of the theory of pathogenesis breast cancer is molecular genetic approaches such as apoptosis gene, oncogen, suppressorgene, and growth promoting factor gene. However, the diagnostic and therapy of breast cancer are still not satisfied. The lost or decreased in the expressionof RAR β2gene on 3p24 chromosome via loss of heterozygosity (LOH) mechanism are the role of pathogenesis of breast cancer. Design of the research is by experimental and observational. Human female breastcancer and blood samples were gained from public hospital RSUD dr. Saiful Anwar, Malang. DNA was extracted from lymphocyte and tissue using Macherey-Nagel system kit. Loss of heterozygosity (LOH) incident in 3p24 chromosome was detected by PCR and Chromogenic in situ Hybridization (CISH) method.